An Underlooked Cause of Periodic Fever (PFAPA) in an Adult Patient with No Response to Tonsillectomy - Fiaz Alam; Mohammed Hammoudeh (Case Reports in Rheumatology)
Periodic fever with aphthous stomatitis, pharyngitis, and adenitis (PFAPA) is an autoinflammatory disease manifested as recurrent febrile episodes associated with one of the following cardinal features: aphthous ulceration, pharyngitis, and cervical adenitis. It was initially described in children and thought to be a disease of pediatric age group. Few adult cases were also reported in the literature. We describe the case of a 39-year-old female affected by PFAPA who presented with a history of febrile episodes associated with aphthous ulceration, stomatitis, and tonsillitis for 4 years. The febrile episodes occurred at a regular interval of 4 weeks and resolved within 5 days. The patient underwent tonsillectomy without any significant improvement. The patient responded only to a single high dose of steroid during the attack. Although PFAPA was initially thought to be a disease of pediatric age group, it should be considered in patients with recurrent febrile illness in all age groups.